Imfluencia del Compuesto Nanotecnologico EF-TABS en los Parámetros Energéticos Del Motor Kama Km178 - Avalos Diaz, Juan Antonio (2017)
This study aimed to investigate the influence of the nanotechnology product EF-TABS on the energy parameters of the engine KAMA KM178, in variable speed and load regimes, realized in the laboratory of motors, test bench MEC. ENERG. 398-UNT. The most outstanding results obtained from this experiment were: 1. The specific fuel consumption (ge) of the KAMA KM178 engine reveals that when mixing Diesel B5 + EF-TABS, in the working area 2520 – 3240 rpm there is a decrease in fuel consumption of 0.56%, working in full load. 2. The behavior of temperatures T. engine, T. exhaust gas, KAMA KM178 engine when mixing the Diésel B5 + EF-TABS in the working zone regime 2520 -3240 rpm gives a lower level of temperature. As a result, the life cycle of the engine and its components is increased and there are fewer emissions of pollutiing gases. 3. Decreases the excess air coefficient un the working zone regime 2520 – 3240 rpm of the KAMA KM178 engine, which generates better combustion due to a better air-fuel mixture. 4. The KAMA KM178 engine has an elasticity of ɜ = 1.45, which indicates that a ɜ < 3 motor is not very elastic; therefore, it delivers low power a low revs.